The Influence of Cognitive Response on Shopping Satisfaction in Australia and Indonesia - Budisantoso, Tjong; Mizerski, Katherine (Kajian Manajemen dan Bisnis, 2009)
This study examines the relationship between cognitive response, the perception of store atmosphere and shopping satisfaction in two countries, Australia and Indonesia. The cognitive response is measured in terms of the perception of merchandise quality and the perception of service quality. The results of factor analysis show measurement invariance on the perception of store atmosphere and the cognitive measurements in Australia and Indonesia.